Biochemical Analysis and Physico Chemical Stability of a Partially Purified Lectin from Hilsha Eggs - Hasan, Imtiaj; Kabir, Syed Rashel; Haque, Md Ashraful; Absar, Nurul (Journal of Bio-Science, 2011)
Context: Hilsha is one of the most popular fish in Bangladesh. Biochemical analysis of Hilsha egg revealed that it is quite a healthful food. A specific class of proteins called lectins is partially purified from this source. Objectives: To carry the nutritional analysis of Hilsha eggs and to isolate sugar-specific lectins from the animal source by applying effective purification techniques. Materials and Methods: The moisture, ash, protein, lipid, polysaccharide, free sugar, cholesterol, calcium, phosphorus and iron contents were determined by the conventional methods and the lectins were isolated by using the affinity chromatographic technique. The effect of temperature, pH and metal ions were observed by performing the hemagglutination assay. Results: The moisture, ash, protein, lipid, polysaccharide, free sugar, cholesterol, calcium, phosphorus and iron contents were 34-, 2.4-, 32.59-, 28.35-, 0.036-, 0.059-, 0.40-, 0.178-, 0.193- and 0.136%, respectively. The partially purified crude protein by affinity chromatography from Hilsha eggs agglutinated rabbit erythrocytes and the hemagglutinating activity is inhibited by 25mM Raffinose followed by 100 mM of glucose, N-acetyl-D-glucosamine, N-acetyl-D-galactosamine and D-galactosamine-HCl each. In the presence of the chelating agent EDTA, the lectin lost its activity completely. Thermal and pH inactivation assay of the lectin indicates that the activity is highest at 30 to 40°C and at the pH 5 to 9, respectively. Conclusion: Hilsha fish eggs can be recommended as a nutritious food and as well as can be regarded as a source of animal lectins, a group of sugar-binding proteins. Key words: Nutritional analysis; Hemagglutination assay; Temperature; pH; Tenualosa ilisha. DOI: 10.3329/jbs.v17i0.7097 J. bio-sci. 17: 35-40, 2009